PENGARUH PARAMETER LAS PADA SAMBUNGAN PLUG WELDING LOGAM TAK SEJENIS ANTARA CARBON STEEL DAN STAINLESS STEEL DENGAN FILLER E308L - Haikal Haikal; Surya Suseno; Moch. Chamim; Isnarno Isnarno (Polinema Press, Politeknik Negeri Malang, 2020)
Plug welding is one of the welding methods of joining material with filling techniques using filler metal. This study aims to determine the effect of variations in electrical current and depth of artificial penetration of Ø8 mm holes on the failure mode and tensile load bearing capacity of dissimilar metal plug welding connections between SS 304 series stainless steels and SS 400 series carbon steels. used are 200, 215 and 230 A while the variation in depth of artificial penetration with diameter of Ø8 mm is 0, 1 and 2 mm. The results of this study indicate that the variation of the welding current without any artificial penetration (0 mm) results in an interfacial failure failure mode. While the existence of artificial penetration with a depth of 1-2 mm produces pull out failure mode. The results of the shear tensile test showed that the highest welding strength was obtained at a variation of 230 A with a hole depth of 1 mm at an average of 12.6 kN while in the hole depth parameters 0 and 2 mm the weld strength values ​​were obtained at a mean of 5.6 and 7.8 kN.